Analisis Nilai Perusahaan dengan Rasio Aktivitas Sebagai Variable Moderating pada Perusahaan Sektor Infrastruktur, Utilitas, dan Transportasi di Bursa Efek Indonesia - Alivka Maulida Anniza; Rahman Amrullah Suwaidi (Ekonomis: Journal of Economics and Business, 2023)
This study aims to see the effect of profitability and capital structure on firm value and the use of activity ratios as moderating variables in infrastructure, utility, and transportation sector companies on the Indonesia Stock Exchange. The total population is all companies in the infrastructure, utility, and transportation sectors on the Indonesia Stock Exchange, which are 56 companies during the 2018-2020 period. Sampling was done by purposive sampling, so the final sample was 46 companies. Moderated Regression Analysis (MRA) is used in testing data with the classical assumption test first with the help of the SPSS 25 application. The results show that profitability can contribute to firm value, the Capital structure has not been able to contribute to firm value, and Activity ratios cannot strengthen the contribution of profitability to firm value. The firm value and activity ratio cannot strengthen the contribution of capital structure to firm value.